Impact of cardiopulmonary resuscitation on a cannot intubate, cannot oxygenate condition: a randomised crossover simulation research study of the interaction between two algorithms. Issue 11 (24th November 2019) - Ott, Thomas; Stracke, Jascha; Sellin, Susanna; Kriege, Marc; Toenges, Gerrit; Lott, Carsten; Kuhn, Sebastian; Engelhard, Kristin
Abstract : Objectives: During a 'cannot intubate, cannot oxygenate' situation, asphyxia can lead to cardiac arrest. In this stressful situation, two complex algorithms facilitate decision-making to save a patient's life: difficult airway management and cardiopulmonary resuscitation. However, the extent to which competition between the two algorithms causes conflicts in the execution of pivotal treatment remains unknown. Due to the rare incidence of this situation and the very low feasibility of such an evaluation in clinical reality, we decided to perform a randomised crossover simulation research study. We propose that even experienced healthcare providers delay cricothyrotomy, a lifesaving approach, due to concurrent cardiopulmonary resuscitation in a 'cannot intubate, cannot oxygenate' situation. Design: Due to the rare incidence and dynamics of such a situation, we conducted a randomised crossover simulation research study. Setting: We collected data in our institutional simulation centre between November 2016 and November 2017. Participants: We included 40 experienced staff anaesthesiologists at our tertiary university hospital centre. Intervention: The participants treated two simulated patients, both requiring cricothyrotomy: one patient required cardiopulmonary resuscitation due to asphyxia, and one patient did not require cardiopulmonary resuscitation. Cardiopulmonary resuscitation was the intervention. Participants were evaluated by video records. Primary outcome measures: The difference in 'time to ventilation through cricothyrotomy' between the two situations was the primary outcome measure. Results: The results of 40 participants were analysed. No carry-over effects were detected in the crossover design. During cardiopulmonary resuscitation, the median time to ventilation was 22 s (IQR 3–40.5) longer than that without cardiopulmonary resuscitation (p=0.028), including the decision-making time. Conclusion: Cricothyrotomy, which is the most crucial treatment for cardiac arrest in a 'cannot intubate, cannot oxygenate' situation, was delayed by concurrent cardiopulmonary resuscitation. If cardiopulmonary resuscitation delays cricothyrotomy, it should be interrupted to first focus on cricothyrotomy.